2022
DOI: 10.1186/s12887-021-03055-7
|View full text |Cite
|
Sign up to set email alerts
|

A very rare case report of glycogen storage disease type IXc with novel PHKG2 variants

Abstract: Background Pathogenic mutations in the PHKG2 are associated with a very rare disease—glycogen storage disease IXc (GSD-IXc)—and are characterized by severe liver disease. Case presentation Here, we report a patient with jaundice, hypoglycaemia, growth retardation, progressive increase in liver transaminase and prominent hepatomegaly from the neonatal period. Genetic testing revealed two novel, previously unreported PHKG2 mutations (F233S and R320Df… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Laboratory tests are unhelpful because the changes are unspeci c and interfere with other hepatic and muscle types (13). Tests reveal fasting hypoglycemia, hepatic enzyme elevation, high serum transaminase, ketosis, cholestasis, increased Plasma cholesterol, triglycerides and total lipids with pathologic glucagon tolerance test (14,11,8,15). Normal uric acid levels, CPK and a slight elevation of plasma aminotransferases usually distinguish type IX from GSD type III (12,17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory tests are unhelpful because the changes are unspeci c and interfere with other hepatic and muscle types (13). Tests reveal fasting hypoglycemia, hepatic enzyme elevation, high serum transaminase, ketosis, cholestasis, increased Plasma cholesterol, triglycerides and total lipids with pathologic glucagon tolerance test (14,11,8,15). Normal uric acid levels, CPK and a slight elevation of plasma aminotransferases usually distinguish type IX from GSD type III (12,17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding treatment, most studies showed that uncooked cornstarch, low_ fat and high_ protein diet are the most helpful treatment for GSD IX patients (14).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it encodes the hepatic isoform of the gamma unit of phosphorylase kinase. People get glycogen storage disease type IXc, a rare and severe phenotype of glycogen storage disease, when PHKG2 is defective [ 16 , 17 ]. The reported research showed that PHKG2 was frequent epigenetic hypermethylation in papillary thyroid cancer [ 18 ].…”
Section: Discussionmentioning
confidence: 99%